Designing aluminium friction stir welded joints against multiaxial fatigue (Fracture and Structural Integrity, 2016)
The present paper investigates the accuracy of the Modified Wöhler Curve Method (MWCM) in estimating multiaxial fatigue strength of aluminium friction stir (FS) welded joints. Having developed a bespoke joining technology, circumferentially FS welded tubular specimens of Al 6082-T6 were tested under proportional and non-proportional tension and torsion, the effect of non-zero mean stresses being also investigated. The validation exercise carried out using the experimental results have demonstrated that the MWCM applied in terms of nominal stresses, notch stresses, and also the Point Method is accurate in predicting the fatigue lifetime of the tested FS welded joints, with its use resulting in life estimates that fall within the uniaxial and torsional calibration scatter bands.
Keywords: Friction stir welding; Multiaxial fatigue; Critical plane